Clinical and epidemiological profile of patients admitted with dengue fever in a tertiary care hospital, Thrissur, Kerala, India - George, Tania; Mankara Valsan, Sruthi (International Journal Of Community Medicine And Public Health, 2020)
Background: Dengue is a fast emerging mosquito borne pandemic prone viral disease affecting many parts of the world. The elucidation of the exact clinical profile is important for patient management and thus crucial for saving life. Dengue is widespread throughout the tropics, with risk factors influenced by local spatial variations of rainfall, temperature, relative humidity, degree of urbanization and quality of vector control. Methods: A descriptive study was undertaken and data was collected by reviewing the records of patients admitted with dengue fever over a period from January 2019 to August 2019. Total 100 records of confirmed cases of dengue were included in the study. The information regarding demographic details, clinical symptoms and complications, and epidemiological details were collected from the records using a questionnaire. Results: Out of 100 patients admitted with dengue, 61% were males and 54% of the total were admitted during June and July month. Most common symptoms reported were fever (99%), headache (91%), muscle & joint pain (71%). The bleeding manifestation was reported in 11% and the most common site of bleeding was gastrointestinal tract. Conclusions: The present study concludes that dengue confirmed cases are seen more among males, and the incidence of disease is more in age groups of less than 30 years. Most of them were residing in the Northern part of Thrissur (56%) and the most common clinical symptoms were fever and headache.